ANALYSIS OF HEAVY METALS (LEAD AND CADMIUM) CONTAINED ON THE ILLUSTRATED CERAMIC PLATE BY ATOMIC ABSORPTION SPECTROPHOTOMETER - Mustarichie, Resmi; Indriyati, Wiwiek; Riokogro, Riajawan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: This study aims to determine whether there are lead (Pb) and cadmium (Cd) metals caused by the dilution of color on a locally illustrated plate. Methods: Illustrated ceramic plates soaked for Â½, 1, and 2 hrs in acidic solution were then measured using atomic absorption spectrophotometer to the availability of Pb and Cd. Results: The results showed that in the three samples of locally made illustrated ceramic plates gave contamination of Pb and Cd. The highest Pb content of metal contamination at the time of Â½ hr immersion in the sample plate of the brand B was equal to 1.2539 ppm. At the time of 1 hr immersion in the sample plate of the brand, C was equal to 0.7737 ppm. The highest Cd content of metal contamination at the time of Â½ hr immersion in the sample plate of the brand B was 0.2690. Conclusion: The results of this study indicated that the locally made illustrated plate could cause pollution of Pb and Cd. These results suggested caution in the use of decorated ceramic plates, especially, for acidic foods and the need for further research for various brands of ceramic plates display in the market.